Assays for cytokines and cytokine assay performance 2 - Whiteside, Theresa (Henry Stewart Talks, 2022)
Types of cytokine assays available, Examples of most widely used cytokine assays, Principles of ELISA and ELISPOT, How to select the right cytokine assay, Multiplex analyses and cytokine profiling, Principles of QA/QC for cytokine assays, Data analysis and pitfalls